Islamic Law and the Meaning of Men's Status in the Bajapuik Padang Pariaman Customs - Zakky Maulana Hadi (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the relationship between Islamic law and the meaning of male status in the Bajapuik custom in Padang Pariaman. The Bajapuik custom is a unique tradition in Minangkabau culture where the woman gives a sum of money to the man as part of the marriage process. This practice often raises debates about its appropriateness and implications in the context of Islamic law. This study uses a qualitative approach with a case study method to analyze the perspectives of the Padang Pariaman community on the Bajapuik custom and the views of Islamic law on the practice. Data were collected through in-depth interviews, participant observation, and document analysis. The results show that although the Bajapuik custom is considered an integral part of the Minangkabau cultural identity, there are various views regarding its appropriateness with the principles of Islamic law. Some religious figures consider it not to be in conflict with sharia as long as it does not violate the principle of mahar (dowry) in Islam, while others argue that this practice needs to be adjusted to be more in line with Islamic teachings. This study contributes to a deeper understanding of the dynamics between customary traditions and Islamic law and their implications for the social status of men in Padang Pariaman society.